Business strategy formulation of three brothers barbershop to increase the cutomer base - Jaya, Surya; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2018)
Abstract – The barbershop industry is still a promising industry because it has good growth. Increasing purchasing power of the people, supported by the ease of disseminating information about lifestyle, fashion, men’s trend, and more through the internet is one of the factors supporting the growth of this barbershop industry. This good growth makes the barbershop business becomes an attractive business for many people. As the result, many new barbershops pops up and makes competition in the barbershop industry even tighter. As a newcomer to the barbershop industry, Three Brothers Barbershop which has been open since August 2017 has difficulty finding its market share, despite its strategic position, which is located at Jalan Karang Tengah Raya, South Jakarta city. It's been a year since its opening, but Three Brothers Barbershop still suffers losses every month. This study aims to help Three Brothers Barbershop formulate its business strategy to find its market share, create a huge customer base, and gain profit. In this research, some internal analysis and external analysis will be conducted. Internal analysis was carried out using Value Chain Analysis and Business Model Canvas methods, while external analysis was carried out using PEST Analysis and Porter Five Forces methods. Results from internal and external analysis will then be summarized in the SWOT method.The results of this study indicates that actually Three Brothers Barbershop has a good assessment of its customers, but the lack of marketing efforts led to Three Brothers Barbershop. Improvements in terms of marketing, both offline and online marketing must be done by Three Brothers Barbershop to gain market share.Keywords: Barbershop industry, business strategy, internal analysis, external analysis